The zeta chain is associated with a tyrosine kinase and upon T-cell antigen receptor stimulation associates with ZAP-70, a 70-kDa tyrosine phosphoprotein. - Chan, A C (1991)
Stimulation of the T-cell antigen receptor (TCR) leads to tyrosine phosphorylation of a number of cellular proteins, including phospholipase C (PLC) gamma 1 and the TCR zeta chain. We describe here a 70-kDa tyrosine phosphoprotein (ZAP-70) that associates with zeta within 15 sec following TCR stimulation. The phosphorylation of ZAP-70 and its association with zeta is independent of the other TCR chains since stimulation of a functional CD8/zeta chimeric receptor in a TCR-negative T cell leads to coprecipitation of ZAP-70 with the chimeric protein. In a Jurkat cell expressing the TCR and the CD8/zeta chimeric protein, tyrosine phosphorylation and association of ZAP-70 occurs exclusively with the stimulated receptor complex. In addition, a tyrosine kinase that does not appear to be fyn associates with the cytoplasmic domain of zeta and phosphorylates zeta and ZAP-70 in vitro.